Best Answer

I can either multiply the brackets out using the distributive law:

(x + 5)5 = (x + 5)(x + 5)(x + 5)(x + 5)(x + 5)

= (x2 + 5x + 5x + 52)(x + 5)(x + 5)(x + 5)

= (x2 + 10x + 25)(x + 5)(x + 5)(x + 5)

= (x3 + 15x2 + 75x + 125)(x + 5)(x + 5)

= (x4 + 20x3 + 150x2 + 500x + 625)(x + 5)

= x5 + 25x4 + 250x3 + 1250x2 + 3125x + 3125

However, this is liable to error, so I'd use the binomial theorem to go there directly:

(p + q)n = Σnr=0 (nr)pn-rqr = (n0)pn + (n1)pn-1q1 + ... + (nn-1)pqn-1 + (nn)qn

Where (nr) = nCr = n!/(n-r)!r!

Thus:

(x + 5)5 = (50)x5 + (51)x45 + (52)x352 + (53)x253 + (54)x54 + (55)55

= 1.x5 + 5.x4.5 + 10.x3.25 + 10.x2.125 + 5.x.625 + 1.3125

= x5 + 254 + 250x3 + 1250x2 + 3125x + 3125

(The dot is used to represent "multiply" as its symbol would look too much like the x.)

Q: How do you solve bracket x plus 5 bracket to the power of 5?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(a + 5) (a - 5) = a2 - 25

2x + 5 - 5 = 2x. You can not solve for x because this is not an equation.

5+y+2y? = 5+3y?

-7p2 -2p3 + 5 is an expression, not an equation or inequality. An expression cannot be solved

You need to solve x before I can answer this

Related questions

2(2*4-5)+6 = 12

0

(a + 5) (a - 5) = a2 - 25

2x + 5 - 5 = 2x. You can not solve for x because this is not an equation.

-2 plus 5 equals +3

+3

3?

5+y+2y? = 5+3y?

A is 14

3

You need to solve x before I can answer this

to solve this one must know the value of x